Digital Body Positivity Activism Role of Influencers on Instagram to Spread Body Positivity Discourse - Ayu Candra Puspita Anzani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the practice of digital body positivity activism on Instagram social media. Instagram social media plays a role in creating a much more democratic space and creating more neutral users. However, in reality, Instagram is one of the mediums where the ideal body and beauty myths continue to be intensified. The presence of body positivity seeks to challenge the beauty myths displayed in various media. The analysis was conducted with several content samples with the hashtags #bodypositive and body positivity. Previous studies have analyzed more positive body image campaigns on social media (Facebook, Instagram, and Twitter) and how other social media users respond to the discourse of body positivity being spread. The results of this study, where body positivity activists and influencers spread body positivity, also take a significant role in spreading body positivity discourse.